Mengungkap Katastrofe Kuno di Yogyakarta Berbasis Indigenous Knowledge dalam Perspektif Filoarkeologi - Arrazaq, Naufal Raffi; Syarqiyah, Indah Nurafani; Hidayat, Sahmu; Prihantoro, Fahmi (Patra Widya: Seri Penerbitan Penelitian Sejarah dan Budaya., 2021)
People of Yogyakarta have an indigenous knowledge about catastrophe that is starting to be abandoned, due to the development of science and technology. Catastrophe events are considered more accurate when examined in a technological perspective, even thought technology has not been able to explain the meaning and philosophy of indigenous communities. The purpose of this research is; (a) identify traces of ancient catastrophe in Yogyakarta based on a philoarchaeological perspectiveand (b) analyze the relationship between the emergence of natural disaster folklore and the potential of natural disasters.The method of data collection is done online. The data were analyzed with a philoarchaeological approach. The results of this study show that ancient catastrophe consists of earthquakes, tsunamis, mountain eruptions, and floods. There is a link between the emergence of folklore and natural disasters. Folklore Ratu Kidul, Labuhan, and Merti Desa are related to earthquakes and tsunamis. Folklore Mbah Petruk, Labuhan, and Merti Desa are related to mountain eruptions.